COVID-19 in Rural India - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
India is the second-worst affected country in the world by COVID-19 pandemic. Although the Government of India took various initiatives to curb the spread of corornavirus in the country which included a 3-week nation-wide lockdown to begin with (from March 25 to April 14) and which later was extended thrice up until May 31, 2020, increasing testing, setting up quarantine facilities, COVID-19 treatment facilities, contact tracing through Aarogya Setu application and many more, but these efforts fell short when it came to supressing the pandemic. Especially, because of lockdown, when the migrant workers were forced to leave cities and travel back to their homes in rural areas, the COVID-19 infection which predominantly affected the urban areas until then also reached rural areas of the country. Overtime, the proportion of COVID-19 cases in rural areas has risen. Rural districts in the states of Andhra Pradesh, Maharashtra, Karnataka, Uttar Pradesh and Assam witnessed a significant rise in COVID-19 cases. Many factors pose a big challenge for rural India in dealing with COVID-19. These include scarcity of medical staff, equipment and health facilities, social stigma, fear of ill-treatment at the health facility, fear of losing income on being quarantined etc. Post-COVID complications are also emerging as a new threat in dealing with the current crisis. Health and Wellness Centres (HWCs) under Ayushman Bharat and Accredited Social Health Activist (ASHA) workers can play a crucial role in dealing with COVID-19 in the rural areas. ASHAs are involved in conducting house-to-house visits, reporting symptomatic cases, carrying out contact tracing, maintaining documentation, monitoring the situation and creating awareness about COVID-19 in the community. But, ASHA workers are facing many challenges such as increased work load, lack of protective equipment and training, they are underpaid, stigmatization, caste discrimination, domestic violence etc. India needs to develop a strategy specific to rural settings to deal with the COVID-19 situation. We believe that at a time when the federal and state governments are dealing with the challenges emanating from the Covid-19 pandemic, this crisis should be seen as an opportunity to strengthen the public health system in India. This would entail, among other things: 1) a much higher level of public health spending; 2) comprehensive training, effective control and oversight and timely and adequate payments for the ASHAs; 3) an effective and efficient management structure for the health facilities at the village, block and district levels; and 4) commensurate physical infrastructure and human resources in the sub-centers and the Primary Health Centers with the growing needs of the regions.
Keywords: 330